2019
DOI: 10.1021/acsami.9b11817
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Passivated SnO2 Electron Transport Layer for High-Performance Perovskite Solar Cells

Abstract: Tin oxide (SnO 2 ) is widely used in perovskite solar cells (PSCs) as an electron transport layer (ETL) material. However, its high surface trap density has already become a strong factor limiting PSC development. In this work, phosphoric acid is adopted to eliminate the SnO 2 surface dangling bonds to increase electron collection efficiency. The phosphorus mainly exists at the boundaries in the form of chained phosphate groups, bonding with which more than 47.9% of Sn dangling bonds are eliminated. The reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 39 publications
0
97
0
Order By: Relevance
“…For example, phosphoric acid can terminate Sn dangling bonds on the surface of the SnO 2 films by forming SnOP bonds. [ 250 ] This reduces the potential barrier induced by O 2− ions which is formed due to the electron capturing of O − from the CB of SnO 2 . Among the reported acids, EDTA made the most notable change compared to the control devices by increasing the PCE by 2.59% absolute and prolonging the shelf stability to 2880 h without encapsulation.…”
Section: Passivation Routes For Sno2 For High‐performance Pscsmentioning
confidence: 99%
“…For example, phosphoric acid can terminate Sn dangling bonds on the surface of the SnO 2 films by forming SnOP bonds. [ 250 ] This reduces the potential barrier induced by O 2− ions which is formed due to the electron capturing of O − from the CB of SnO 2 . Among the reported acids, EDTA made the most notable change compared to the control devices by increasing the PCE by 2.59% absolute and prolonging the shelf stability to 2880 h without encapsulation.…”
Section: Passivation Routes For Sno2 For High‐performance Pscsmentioning
confidence: 99%
“…[ 25 ] To diminish the Sn dangling bonds, Jiang et al applied phosphate‐passivated SnO 2 as ETLs, which improved the PCE of PSCs from 19.67% to 21.02%. [ 24 ] Jung et al used NH 4 F surface treatment to reduce the defect sites on the SnO 2 surface and obtained a higher PCE. [ 15 ] Furthermore, Liu et al modified SnO 2 by ethylene diamine tetra‐acetic acid (EDTA) chelating agent to realize an EDTA‐complexed SnO 2 ETL, which shows more superior electronic properties than the pristine SnO 2 ETLs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 78 ] Jiang et al also reported similar conductivity enhancement while passivating phosphate in the SnO x lattice (architecture: glass/ITO/phosphate passivated SnO x /Ag). [ 37 ] Recently, Liu et al reported a similar conductivity enhancement for Ta‐doped SnO x (≈4.7 × 10 −6 S cm −1 which is much higher than bare SnO x films, ≈2.4 × 10 −6 S cm −1 ) and this results in a 1% higher device efficiency in the case of Ta‐doped SnO x when compared with pristine SnO x . [ 34 ] Similarly, Akin et al reported that Ru‐doped SnO x show enhanced conductivity, 2.7 × 10 −5 S cm −1 which is better than pristine SnO x (1.4 × 10 −5 S cm −1 ).…”
Section: Resultsmentioning
confidence: 92%
“…Electropositive molecules like phosphoric acid, acetic acid, and electronegative molecules like (NH 4 ) 2 S are used to control the corresponding defects on the SnO x surface. [ 37–39 ] Similarly, BMIMBF 4 (BMIM + , BF 4 − ), NH 4 Cl (NH 4 + Cl − ), and KCl (K + Cl − ) molecules were used to simultaneously passivate electropositive and electronegative defects present in the SnO x lattice by means of their individual cations and anions. [ 40–43 ]…”
Section: Introductionmentioning
confidence: 99%